Spurring vaccine development for the developing world: a collaborative governance perspective on product development partnerships - Hayter, Christopher S.; Nisar, Muhammad Azfar (2018)
Collaborative governance has emerged recently as an alternative to the traditional sector-based, single-actor approaches for addressing complex governance challenges. However, previous research has given little attention to collaborative governance within international policy contexts. To address this gap, an integrative collaborative governance framework is used to analyze product development partnerships (PDPs) that seek to develop vaccines to prevent the spread of devastating diseases within the developing world. The analysis indicates that PDPs are helping address acute governance challenges and are emblematic of the increasing importance of nonprofit organizations in collaborative governance regimes. Implications for research on collaborative governance are also discussed. - Reproduced.
Keywords: Collaborative governance; Drugs; Heatlh services; Public administration; Vaccination